A Novel Tangential Electric-Field Sensor Based on Electric Dipole and Integrated Balun for the Near-Field Measurement Covering GPS Band - Jianwei Wang; Zhaowen Yan; Wei Liu; Donglin Su; Xin Yan (Sensors, 2019)
This paper presents a novel tangential electric-field sensor with an embedded integrated balun for sensing up a tangential electric field over a circuit surface in the near-field measurements covering the GPS band. The integrated balun is embedded into the sensor to transform the differential voltage induced by the electric dipole into the single output voltage. The measurement system with a high mechanical resolution for the characterizations and tests of the sensor is detailed in this paper. The frequency response of the sensor characterized by a microstrip line from 1.35 GHz to 1.85 GHz (covering the GPS band) is rather flat. The rejection to the magnetic field of the sensor is up to 20.1 dB. The applications and validations of the sensor are conducted through passive/active circuit measurements.